Peran Organisasi Kemahasiswaan dalam Penguatan Demokrasi Mahasiswa di FKIP Universitas Riau - Saradilla, Ella; Darmawan, Muhammad Ikhsan; Nainggolan, Nora Saurli; Simatupang, Indah Lamtiur; Ridho, M.Rasyid; Azila, Wan Fazila; Hasibuan, Hamdi Abdullah (Pancasila and Civics Education Journal, 2025)
ABSTRACTParticipatory democracy is one of the important indicators in realizing a democratic, fair, and inclusive campus life. Student organizations have a strategic role in fostering political awareness and forming active and critical student characters. This study aims to analyze the role of student organizations at the Faculty of Teacher Training and Education (FKIP) of Riau University in strengthening participatory democracy among students. The method is descriptive research with data collection in the form of observations, interviews, and documentation studies of organizational administrators and active students. The results of the study show that organizations such as BEM, DPM, and HIMA have contributed to political education, advocacy, and the formation of social participation values through various work programs. However, student participation is still low due to various factors such as apathy, lack of program innovation, and changes in the social preferences of the younger generation. In conclusion, the role of FKIP student organizations is quite significant, but needs to be optimized through a more creative and adaptive approach so that participatory democracy in the campus environment can develop more substantially.Keywords: Student Organizations, Participatory, DemocracyABSTRAKDemokrasi partisipatif merupakan salah satu indikator penting dalam mewujudkan kehidupan kampus yang demokratis, adil, dan inklusif. Organisasi kemahasiswaan memiliki peran strategis dalam menumbuhkan kesadaran politik serta membentuk karakter mahasiswa yang aktif dan kritis. Penelitian ini bertujuan untuk menganalisis peran organisasi mahasiswa di Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Riau dalam penguatan demokrasi partisipatif di kalangan mahasiswa. Metodenya adalah penelitian deskriptif dengan pengumpulan data berupa observasi, wawancara, dan studi dokumentasi terhadap pengurus organisasi dan mahasiswa aktif. Hasil penelitian menunjukkan bahwa organisasi seperti BEM, DPM, dan HIMA memiliki kontribusi dalam pendidikan politik, advokasi, serta pembentukan nilai partisipasi sosial melalui berbagai program kerja. Namun, partisipasi mahasiswa masih rendah akibat berbagai faktor seperti apatisme, kurangnya inovasi program, dan perubahan preferensi sosial generasi muda. Kesimpulannya, peran organisasi mahasiswa FKIP cukup signifikan, tetapi perlu dioptimalkan melalui pendekatan yang lebih kreatif dan adaptif agar demokrasi partisipatif di lingkungan kampus dapat berkembang secara lebih substansial. Kata Kunci: Organisasi Kemasiswaan, Partisipatif, Demokrasi